DISTRIBUSI INFEKSI PENYAKIT WHITE SYNDROMES DAN KARANG MEMUTIH (CORAL BLEACHING) PADA KOMUNITAS KARANG KERAS DIPULAU PETONDAN TIMUR, KEPULAUAN SERIBU - Safran Yusri; Estradivari Estradivari (Research Center for Biology-Indonesian Institute of Sciences, 2007)
Currently, there are few information regarding the infection of diseases to corals in Seribu Islands, DKI Jakarta, Indonesia, eventhough scientists have suspected that coral diseases and coral bleaching event would occur in the area due to the pollution from Jakarta. In April 17 - 22 2006, a survey was done in Petondan Timur as a response of oil spill incident in the previous month. Results show that 3.9% of coral colony from 16 genera were infected with white syndromes (WS), with 2,1% bleached. This is a shocking result because no infection were found in February 2006.Acroporids and Pocilloporids were the most affected with WS. The infection also occurs more in the shallow area (3 m).It also seems that the infection correlates with coral bleaching.This phenomenon is suggested to happen due to the combination of oil spill incident and seasonal transition.